Discovery Learning Model to Improve Critical Thinking Ability of Class V Elementary School Students - Erna Nurhayati (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve the critical thinking skills of class V students in science learning with the Discovery Learning learning model. The research undertaken was a Classroom Action Research with 3 cycles, with each cycle consisting of one meeting. The stages of each cycle are planning, implementing, observing, and reflecting. In cycle I students who have high critical thinking skills are 60%, in cycle II there is an increase to 85%, and in cycle III it increases to 90%. With a level of mastery learning 65% in cycle I, 80% in cycle II, and increased to 90% in cycle III. The final conclusion from the implementation of this classroom action research is that the use of discovery learning models can improve students' critical thinking skills in science learning human digestive organs in SD Negeri Ciwalen 03, Dayeuhluhur District, Cilacap Regency.